Characterization of the Pre and Post Blast Environments - Jack Elorenta (International Society of Explosives Engineers, 2003)
We often hear that, "Blasting was an art, but now blasting is now a science". 'Scientific' blasting implies that we have quantified and reproducible measurements of the feedstock and product of the blasting process. However, the industry's reluctance to adopt two key technologies, drill monitoring and optical size analyzers, sheds doubt on the claims of scientific blasting.